High Dose Vitamin D, Digoxin, and BiDil Reverse Congestive Heart Failure in a Critically ILL Trauma Patient and a Severely Obese Male Patient - L Ray Matthews; Yusuf Ahmed; Omar Danner; Carolyn Moore; Carl Lokko; Jonathan Nguyen; Keren Bashan-Gilzenrat; Diane Dennis- Griggs; Nekelisha Prayor; Peter Rhee; Ed Childs; Kenneth Wilson (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Presently, the prevalence of congestive heart failure in the United States is 6.5 million people. We report two cases of severe congestive heart failure patients with a very poor prognosis, treated successfully with a combination of high dose vitamin D, digoxin, and BiDil (Matthews' Two Inotrope Protocol). Further studies are needed to fully appreciate the overall healthcare changes associated with this simple drug therapy.